(untitled) (Research, Society and Development, 2022)
Objective: Evaluation of various bulk-fill composite materials with respect to the microhardness values of the top and base surfaces upon variation in the composite thickness. The effect of aging and comparison of the fluorescence properties exhibited by the materials at different thicknesses will also be examined. Materials and Methods: For all samples, calculations were carried out using a family F probability, with a repeated family design including interactions within and among the factors, which resulted in 135 sample units, with 27 samples per experimental group. Z350, AURA, TETRIC, SDR, and FBF composites were employed with thicknesses of 2, 3, and 4 mm, initially being submitted to microhardness measurements (n=9). Aging was carried out using an aqueous ethanol solution. After aging the microhardness values of the samples were measured again, and a comparative analysis was performed for the fluorescence of all samples. Results: Aging, sample thickness, and the type of material were found to affect both the surface microhardness and the fluorescence values. In addition, the AURA and SDR bulk-fill composites were the least susceptible to differences in thickness in terms of the top and base surface microhardness values. Conclusions: Although the manufacturers of some bulk-fill composites recommend the use of material increments of 4 mm, the results of this study suggest that further research is required before clinical application.